The Crosstalk Between Epigenetic Mechanisms and Alternative RNA Processing Regulation - Zhang, Jian; Zhang, Yi-Zhe; Jiang, Jing; Duan, Cheng-Guo (Frontiers in Genetics, 2020)
As a co-transcriptional process, RNA processing, including alternative splicing and alternative polyad-enylation, is crucial for the generation of multiple mRNA isoforms. RNA processing mechanisms are widespread across all higher eukaryotes and play critical roles in cell differentiation, organ development and disease response. Recently, significant progresses have been made in understanding the mechanism of RNA processing. RNA processing is regulated by trans-acting factors such as splicing factors, RNA-binding proteins and cis-sequences in pre-mRNA, and increasing evidence suggests that epige-netic mechanisms, which are important for the dynamic regulation and state of specific chromatic re-gions, are also involved in co-transcriptional RNA processing. In contrast, recent studies also suggest that alternative RNA processing also has a feedback regulation on epigenetic mechanisms. In this re-view, we discuss recent studies and summarize the current knowledge on the epigenetic regulation of alternative RNA processing. In addition, a feedback regulation of RNA processing on epigenetic regu-lators is also discussed.